Modeling of cation diffusion in oxygen ion conductors using molecular dynamics - Kilo, M. (2004)
Cation diffusion in ionic conducting oxides is modelled using molecular dynamics (MD). As example systems LSGM (Sr- and Mg-doped LaGaO3; perovskite structure) and YSZ (Y-doped ZrO2; fluorite structure) were investigated. In both systems, cation diffusion is governed by diffusion via lattice vacancies and not via interstitials. In LSGM, the diffusion of all types of cations is correlated by the formation of a binary vacancy complex of two neighbouring vacancies on the A and B sites of the perovskite lattice, which are migrating together. This leads to very similar cation diffusion coefficients for all four cations. In YSZ, calculated diffusion coefficients of the two cations differ significantly (Y is five times faster than Zr), in good agreement with experiments. The calculated activation enthalpies were close to the experimental ones, indicating that cation diffusion is mainly governed by the migration enthalpy, while the formation enthalpy of a cation vacancy should be small. © 2004 Elsevier B.V. All rights reserved.